Diseño del Sistema de Costos por órdenes de producción en la Corporación de Productores y Comercializadores Orgánicos Bio Taita Chimborazo COPROBICH de la parroquia Cajabamba, cantón Colta, provincia Chimborazo, año 2019 - Ati Inga, Marlene Elena (2020)
The present research work, developed in the Corporation of Organic Producers and Marketers Bio Taita Chimborazo, Cajabamba parish, Canton Colta, Chimborazo province, was implemented the Design of the Cost System for Production Orders, through the corresponding information, which allowed identifying the flaws in determining the costs of the raw material that is processed in the entity.Thus, when using the system, the purpose is to establish sales prices and adequate profit margin for the products that the Corporation offers to its clients, it was executed through field research, documentary, inductive and deductive methods, in the same way using technique such as the survey applied to the operational staff, the survey to the administrative staff of the entity. Therefore, the Corporation does not exercise the respective control and registration of cost elements such as raw material, labor and indirect manufacturing costs as well as operating expenses, for this reason at the time of establishing prices and margin of adequate utility; For this reason, when proposing the cost system in the entity, they will have real, timely, reliable and reasonable information for the improvement of effective and efficient decision-making in production costs, therefore the certainty of setting product prices In addition, keep track of the three cost elements for the elaboration of the final product, in this way to achieve the determination of the sale price and profitability indicators, which will allow you to be competent within the national and international market. Keywords: System, Production, Profitability, Costs, Utility.